The Cost of Equity Field in the Market Projection Companies - Abdulrasool Abaulabbas Sahib, Jasim Mohammed Hussein, Mahdi Atiyah mohi, (Opción, 2019)
The aim of the study is to investigate determinants of the cost of Equity Field study in sample from the companies graduated in market projection for the papers financial via Capital Asset Pricing Model (CAPM) to calculate the cost of equity. As a result, share market price and times interest earned have significant impact on cost of equity. In conclusion, this indicates that financial markets in sultanate of Oman are more volatile with respect to any information.